L’atelier du théâtre étudiant ou comment parler roumain et se faire comprendre par des Français - Nora-Sabina Neamt (Recherches)
“The Student Drama Workshop”, as an innovative Romanian language-teaching strategy, consisted in the original re-writing and performance of a theatre play in Romance languages, according to oral intercomprehension principles. Our aim is to highlight the advantages of this exercise based on the experience of students who took on the roles of writers, actors, and event organizers. The students’ testimonies confirm the consolidation of their linguistic, social and organizational skills, along with the influence of this artistic adventure, and the impact on their personal development.